Image integration into 3-dimensional-electro-anatomical mapping system facilitates safe ablation of ventricular arrhythmias originating from the aortic root and its vicinity. Issue 3 (7th March 2017) - Jularic, Mario; Akbulak, Ruken Özge; Schäffer, Benjamin; Moser, Julia; Nuehrich, Jana; Meyer, Christian; Eickholt, Christian; Willems, Stephan; Hoffmann, Boris A
Abstract: Aims: During ablation in the vicinity of the coronary arteries establishing a safe distance from the catheter tip to the relevant vessels is mandatory and usually assessed by fluoroscopy alone. The aim of the study was to investigate the feasibility of an image integration module (IIM) for continuous monitoring of the distance of the ablation catheter tip to the main coronary arteries during ablation of ventricular arrhythmias (VA) originating in the sinus of valsalva (SOV) and the left ventricular summit part of which can be reached via the great cardiac vein (GCV). Methods and results: Of 129 patients undergoing mapping for outflow tract arrhythmias from June 2014 till October 2015, a total of 39 patients (52.4 ± 18.1 years, 17 female) had a source of origin in the SOV or the left ventricular summit. Radiofrequency (RF) ablation was performed when a distance of at least 5 mm could be demonstrated with IIM. A safe distance in at least one angiographic plane could be demonstrated in all patients with a source of origin in the SOV, whereas this was not possible in 50% of patients with earliest activation in the summit area. However, using the IIM a safe position at an adjacent site within the GCV could be obtained in three of these cases and successful RF ablation performed safely without any complications. Ablation was successful in 100% of patients with an origin in the SOV, whereas VAs originating from the left ventricular summit could be abolished completely in only 60% of cases. Conclusion: Image integration combining electroanatomical mapping and fluoroscopy allows assessment of the safety of a potential ablation site by continuous real-time monitoring of the spatial relations of the catheter tip to the coronary vessels prior to RF application. It aids ablation in anatomically complex regions like the SOV or the ventricular summit providing biplane angiograms merged into the three-dimensional electroanatomical map.